Effect of Birth Interval on Neonatal and Post Neonatal Mortality in Bangladesh (Dhaka University Journal of Science, 2017)
This study investigates the relationship between previous birth interval and infant mortality using the data extracted from the Bangladesh Demographic and Health Survey (BDHS), 2011. For the purpose of regression analysis, the Cox proportional hazard model has been used. Results demonstrate significant effects of previous birth interval on neonatal mortality, but not on post neonatal mortality. If the previous birth interval is less than two years or greater than three years, the index child experiences high risk of neonatal mortality.Dhaka Univ. J. Sci. 65(1): 35-39, 2017 (January)